1981
DOI: 10.1016/0014-4827(81)90310-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aphidicolin, an inhibitor of DNA replication, on sea urchin development

Abstract: SUMMAR Y Aphidicolin, an inhibitor ofDNA polymerase a. arrests DNA synthesis without affecting RNA and protein synthesis at ail stages of sea urchin development. Cleavage is quickly stopped and hatching is prevented by the présence of the drug at 2 /u,g/ml. Treatment with aphidicolin of young blastulae prevents gastrulation. but inhibition of archenteron invagination and skeleton formation is incom plète when the drug is added to late blastulae or early gastrulae. The rôle of cell division in gastrulation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
3
16
1
Order By: Relevance
“…Kobayakawa & Kubota (1981) concluded that, in newt embryos, the timing of the onset of gastrulation is not controlled by the timing of MBT or the total number of cells or cell divisions but, possibly, by the absolute time from fertilization. This finding is consistent with other reports showing that gastrulation began, and was often completed, in amphibian and echinoderm embryos in the absence of nuclear replication and cell division when administered with inhibitors from around the presumptive start of gastrulation (Cooke 1973; Brachet & de Petrocellis 1981; Stephens et al . 1986; Harris & Hartenstein 1991; Rollin & Andrews 1991).…”
Section: Introductionsupporting
confidence: 93%
“…Kobayakawa & Kubota (1981) concluded that, in newt embryos, the timing of the onset of gastrulation is not controlled by the timing of MBT or the total number of cells or cell divisions but, possibly, by the absolute time from fertilization. This finding is consistent with other reports showing that gastrulation began, and was often completed, in amphibian and echinoderm embryos in the absence of nuclear replication and cell division when administered with inhibitors from around the presumptive start of gastrulation (Cooke 1973; Brachet & de Petrocellis 1981; Stephens et al . 1986; Harris & Hartenstein 1991; Rollin & Andrews 1991).…”
Section: Introductionsupporting
confidence: 93%
“…When applied to free-swimming blastulae, DNA-targeting drugs did not induce any changes in swimming pattern, except for the lethal concentrations resulting in embryo immobilization and death. Similar effects of aphidicolin (an inhibitor of DNA polymerase a) (32), 5-azacytidine (an inhibitor of DNA methylation) (33), and DNA intercalator doxorubicin (11) have been observed on sea urchin S. granularis, Psammechinus miliaris, A. punctulata , and P. lividus embryos. These results further supported our observation that the embryo spinning phenomenon is unique to the tubulin destabilizing drugs.…”
Section: Discussionmentioning
confidence: 66%
“…By 48 hr many of the embryos exposed to 100 ppm MXC displayed abnormal gut formation. Since Bresch and Arendt (1977) have reported MXC to inhibit DNA synthesis in early sea urchin embryos and DNA synthesis inhibitors such as aphidicolin have been shown to inhibit gut formation in sea urchin embryos (Stephens et al, 1986;Brachet and De Petrocellis, 1981), it is conceivable that this may be the basis of the failure of gut formation in these MXC-exposed embryos.…”
Section: Discussionmentioning
confidence: 97%